2004
DOI: 10.1080/02841850410005039
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter evaluation of a new laser guidance system for computed tomography intervention

Abstract: Different users at four different centers found the laser guidance system useful and easy to use. A high level of accuracy of the puncture angle was obtained in most cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 14 publications
0
10
1
Order By: Relevance
“…A review of new targeting systems is beyond the scope of this article; however, advanced targeting techniques are being developed for CT, US, and MR imaging (155)(156)(157)(158)(159)(160)(161). Improvements in the ability to better characterize tissue specimens are also on the horizon.…”
Section: Future Considerations and Research Directivesmentioning
confidence: 97%
“…A review of new targeting systems is beyond the scope of this article; however, advanced targeting techniques are being developed for CT, US, and MR imaging (155)(156)(157)(158)(159)(160)(161). Improvements in the ability to better characterize tissue specimens are also on the horizon.…”
Section: Future Considerations and Research Directivesmentioning
confidence: 97%
“…B CT image of needle puncturing the lung nodule 1 Th11 17 15 6 2 L1 40 8 0 3 L1 33 7 3 4 L1 30 9 3 5 L1 35 0 3 6 Th10 35 15 0 7 Th12 29 9 3 8 L2 30 7 0 9 Th12 32 3 3 10 L2 28 4 0 eles et al in 1997, 11 Ishizaki et al in 1998, 12 and Brabrand et al in 2004. 13 Miaux et al and Ishizaki et al developed a device to perform punctures by attaching the laserguided puncture system to the gantry. However, we speculate that the device can get in the way of the gantry when the radiologist advances a puncture needle.…”
Section: Discussionmentioning
confidence: 99%
“…Prior evaluations of other laser-guidance systems for CT interventions reported that the usefulness of the guidance device was dependent on the level of experience of the individual physician [39], [40]. Hereby, especially beginners profited by laser guidance systems for standard procedures while experienced interventionalists gained technical help in complex cases.…”
Section: Discussionmentioning
confidence: 99%